1999
DOI: 10.2527/1999.77123208x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed intake on antimicrobially induced increases in porcine serum insulin-like growth factor I.

Abstract: This study was conducted to determine whether an antimicrobially induced (ASP-250) increase in serum IGF-I was the result of differences in feed intake. Serum IGF-I concentrations were measured in crossbred pigs that were fed a control diet or a diet supplemented with ASP-250 either for ad libitum consumption or limited to 85% of the control pigs' consumption. The pigs that consumed either diet ad libitum, control or ASP-250, consumed similar quantities of feed. The ASP-250 ad libitum-intake pigs had serum IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Manzanilla et al (2006) suggested that the increase in G:F found in pigs fed butyrate may be due to increased activation of the IGF-I axis. Indeed, studies in which antibiotics have been found to increase G:F have found an increase in plasma IGF-I (Hathaway et al, 1996(Hathaway et al, , 1999. Nonetheless, results of our experiment confirm that LPS challenge increases muscle cytokine expression in the pig, as found in rodents (Frost et al, 2002;Lang et al, 2003).…”
supporting
confidence: 82%
“…Manzanilla et al (2006) suggested that the increase in G:F found in pigs fed butyrate may be due to increased activation of the IGF-I axis. Indeed, studies in which antibiotics have been found to increase G:F have found an increase in plasma IGF-I (Hathaway et al, 1996(Hathaway et al, , 1999. Nonetheless, results of our experiment confirm that LPS challenge increases muscle cytokine expression in the pig, as found in rodents (Frost et al, 2002;Lang et al, 2003).…”
supporting
confidence: 82%
“…In particular, butyrate is involved in the regulation of the IGF axis in different tissues (Nishimura et al, 1998;Tsubaki et al, 2001). Hathaway et al (1999) defined increases in IGF-I as a consequence of AGP usage, and they proposed this mechanism as a possible mechanism of action for AGP. The study of this mechanism could also be of interest for butyrate.…”
Section: Productive Performance and Digestionmentioning
confidence: 99%
“…Pigs were bled between 1100 and 1200 h on d 0, 6, 14, 21, and 27. Based on previous studies (Hathaway et al, 1999) one blood sample pig −1 ؒwk −1 was considered adequate to reflect treatment effects. Blood samples were allowed to clot at 4°C for 24 h. Serum was harvested and stored at −80°C.…”
Section: General Methodsmentioning
confidence: 99%
“…Previous studies have shown that weanling pigs fed subtherapeutic levels of an antimicrobial grow faster, more efficiently, and have higher circulating concentrations of insulin-like growth (IGF)-I than pigs fed the same diet without the antimicrobial (Hathaway et al, 1996;Hathaway et al, 1999). Additionally, our studies and those of others have shown that circulating levels 1456 contrast to the effect of weaning on serum IGFBP-3 level, serum IGFBP-2 levels increased on d 6 and d 14 after weaning (P < 0.05) and decreased to preweaning levels by d 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation